2009
DOI: 10.1111/j.1525-139x.2009.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax and Chylopericardial Tamponade in a Hemodialysis Patient with Catheter‐Induced Superior Vena Cava Stenosis

Abstract: Chylothorax and chylopericardium refer to the presence of milky, triglyceride-rich chylous fluid in the thoracic and pericardial spaces, respectively. Both conditions are extremely uncommon in end-stage renal disease patients on dialysis. We report the first known case of combined chylothorax and chylous pericardial tamponade in a dialysis patient associated with catheter-induced superior vena cava (SVC) stenosis. A successful outcome was achieved with drainage of both chylous effusions in combination with ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In the present case, there was an increase in the central venous pressure due to thrombosis and stenosis. This elevated pressure led to an increase in the thoracic duct luminal pressure and subsequently chyle leakage from pleural and pericardial lymphatics causing the chylopericardium and chylothorax 5 . The previous indwelling line was probably the major factor for thrombosis in the present patient, but patients can have hypercoagulability following allogenic HSC transplant 6 .…”
Section: Discussionmentioning
confidence: 73%
“…In the present case, there was an increase in the central venous pressure due to thrombosis and stenosis. This elevated pressure led to an increase in the thoracic duct luminal pressure and subsequently chyle leakage from pleural and pericardial lymphatics causing the chylopericardium and chylothorax 5 . The previous indwelling line was probably the major factor for thrombosis in the present patient, but patients can have hypercoagulability following allogenic HSC transplant 6 .…”
Section: Discussionmentioning
confidence: 73%
“…In 1936, Blalock et al (19) reported chylothorax in response to SVC occlusion in dogs. Since that time, a number of studies have described chylothorax after SVC obstruction (20)(21)(22)(23). Patients who undergo cardiac or thoracic surgery and ECMO may be at risk for the first two mechanisms.…”
Section: Ecmo Svc Obstruction and Chylothoraxmentioning
confidence: 98%
“…[1] Chylothorax can be left-sided (33.3%) when due to damage above the fifth thoracic vertebra, right-sided (50%) when due to thoracic duct damage below this level, or bilateral (16.7%). [2] Other causes include malignancy, cardiac failure, sarcoidosis, goiter, as well as thoracic and upper gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%